Limits of the magneto-optical properties of Bi: YIG films prepared on silica by metal organic decomposition. Issue 17 (1st December 2019) - Nadinov, Issatay; Kovalenko, Oleksandr; Rehspringer, Jean-Luc; Vomir, Mircea; Mager, Loïc
Abstract: Different bismuth-substituted yttrium iron garnet thin films were prepared on silica substrates by metal organic decomposition of propionic salts with varied initial amounts of bismuth, annealing time, and temperature. The magneto-optical properties were monitored continuously during the annealing step, yielding access to the activation energy of the garnet film crystallization. These measurements coupled with X-ray diffraction spectra of the final products show that the magneto-optical properties of the films deposited on silica are limited by the saturation of bismuth substitution and appearance of side products with high initial bismuth contents.